FOUNDATIONS FOR IMPROVING THE ACTIVITIES OF SERVICE SECTOR ENTITIES IN NEW UZBEKISTAN - Shermatova Nargiza Zafar qizi (Western European Studies, 2025)
This article analyzes the main directions for improving the activities of service sector entities in New Uzbekistan. Ongoing economic reforms, digital transformation processes, and the liberalization of the business environment significantly influence the expansion of the service market.Efficient organization of service providers’ activities, the introduction of innovations, and modernization of management systems are considered key factors in this process. The article examines the share of small business and private entrepreneurship in the service sector, along with state support mechanisms and institutional changes. The changing needs of the population, as well as the rapid development of tourism, logistics, financial and digital services, contribute to the diversification of the service segment.The study proposes improving sector efficiency through modern management technologies, digitalization, human capital development, and the implementation of quality standards.Strategic directions aimed at strengthening the competitiveness of service entities are substantiated.The practical significance of the paper lies in the applicability of its conclusions for service sector enterprises
Keywords: Service sector; new Uzbekistan; digitalization; innovation development